Description of orthotic properties and effect evaluation of ankle-foot orthoses in non-spastic calf muscle weakness - Niels F.J. Waterval; Merel-Anne Brehm; Jaap Harlaar; Frans Nollet
Objective: To describe the orthotic properties and evaluate the effects of ankle-foot orthoses for calf muscle weakness in persons with non-spastic neuromuscular disorders compared with shoes-only. Design: Cross-sectional study. Subjects: Thirty-four persons who used ankle-foot orthoses for non-spastic calf muscle weakness. Methods: The following orthotic properties were measured: ankle-foot orthosis type, mass, and ankle and footplate stiffness. For walking with shoes-only and with the ankle-foot orthoses, walking speed, energy cost and gait biomechanics were assessed. Results: Four types of ankle-foot orthosis were identified: shaft-reinforced orthopaedic shoes (n = 6), ventral ankle-foot orthoses (n = 10), dorsal leaf ankle-foot orthoses (n = 12) and dorsiflexion-stop ankle-foot orthoses (n = 6). These types differed significantly with regards to mass, ankle-and footplate stiffness. Compared with shoes-only, all ankle-foot orthoses/orthopaedic shoes groups combined increased walking speed by 0.18 m/s (95% confidence interval (95% CI) 0.13-0.23), reduced energy cost by 0.70 J/kg/m (95% CI 0.48-0.94) and limited ankle dorsiflexion by -3.0° (95% CI 1.3-4.7). Higher ankle-foot orthoses ankle stiffness correlated with greater reductions in walking energy cost and maximal ankle dorsiflexion angle. Conclusion: Ankle-foot orthoses for persons with non-spastic calf muscle weakness vary greatly in properties and effects on gait. The large variation in effectiveness may be due to differences in ankle stiffness, although this requires further prospective evaluation.